Benchmarking information aggregation in experimental markets - Albertazzi, Andrea; Mengel, Friederike; Peeters, Ronald (Economic inquiry, 2021)
Theoretical and experimental literature have provided mixed insights on the ability of financial markets to perfectly aggregate private information into asset prices. We conduct an experiment designed to benchmark information aggregation in markets. In our lab experiment, we randomly assign subjects to different institutional environments, either a market or a Becker–DeGroot–Marschak mechanism. We find evidence that market interaction is worse for information aggregation. The difference between the two environments is driven by price‐insensitive traders who seem unable to learn from market prices. Price‐sensitive traders, by contrast, learn equally well in both environments.